Negative impressions of childbirth in a North-West England student population - Gill Thomson; Kathrin Stoll; Soo Downe; Wendy A. Hall (Taylor & Francis Group, 2017)
Background: Sociocultural childbirth representations can influence the perceptions of childbirth negatively. In this paper we report on a survey study to explore the factors associated with negative impressions of childbirth in a North-West England University student sample. We also explored whether different sources and perceptions of childbirth information were linked to fear of childbirth. Methods: All students received a survey link via an online messaging board and/or direct e-mail. Female students who were 18-40 years of age and childless (but planned to have children in the future) were invited to participate. Demographics, birth preferences, a fear of birth and general anxiety measures were included as well as questions about what sources of information shaped students' attitudes toward pregnancy and birth (i.e. visual/written media, experiences of friends/family members, school-based education and other) and impressions of birth from these sources (i.e. positive, negative, both positive and negative and not applicable). Results: Eligible students (n = 276) completed the online questionnaire. The majority were Caucasian (87%) with a mean age of 22.6 years. Ninety-two students (33.3%) reported negative childbirth impressions through direct or vicarious sources. Students with negative birth impressions were significantly more likely to report higher fear of birth scores. Negatively perceived birth stories of friends/family members, and mixed perceptions of visual media representations of birth were associated with higher fear of birth scores. Having witnessed a birth first-hand and describing the experience as amazing was linked to lower fear scores. Conclusion: First-hand observations of birth, especially positive experiences, had implications for salutary outcomes. Negative or conflicting perceptions of vicarious experiences were associated with increased levels of childbirth fear. While further research is needed, these insights suggest a need for positive birth stories and messages to be disseminated to mitigate any negative effects of indirect accounts.